Variasi Kemampuan Media Zeolit Dalam Menurunkan Kesadahan Air - Muntu, Ronny; Rahmadhany, Restu (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
In principle, hardness is water that is contaminated with cationic elements such as Na, Ca, Mg. In the most common hardness is sea water. In surface fresh water, Ca and Mg generally contain high levels (> 200 ppm) of CaCO3. The purpose of this study was to determine the ability of zeolite media to reduce water hardness. The results of this study can prove that processing using zeolite with a thickness of 30 cm in well water can be said to reduce hardness. In replication I there was a decrease of 9.9%, replication II decreased by 35.2% and in replication III it decreased by 36.5%, while at a media thickness of 55 cm replication I obtained results of 21.3%, replication II of 28.3%, and in replication III there was a decrease of 39.4%, and at a media thickness of 80 cm, replication I obtained a result of 13.5%, replication II obtained a result of 43.7%, and in replication III there was a decrease of 79.9 %. Water is one of the natural resources that has an important function for human life and for advancing general welfare so that it becomes a major capital and the main factor of development.. Keywords : Media; Zeolite; Hardnes